2022
DOI: 10.3389/fpsyt.2022.995834
|View full text |Cite
|
Sign up to set email alerts
|

Risks of suicide among family members of suicide victims: A nationwide sample of South Korea

Abstract: ObjectiveIdentifying the risks of completed suicide in suicide survivors is essential for policies supporting family members of suicide victims. We aimed to determine the suicide risk of suicide survivors and identify the number of suicides per 100,000 population of suicide survivors, bereaved families of traffic accident victims, and bereaved families with non-suicide deaths.MethodsThis was a nationwide population-based cohort study in South Korea. The data were taken from the Korean National Health Insurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Agerbo found that among suicide-bereaved individuals in Denmark, men face a suicide mortality risk three times higher than that of women ( 47 ). However, subsequent studies ( 46 , 48 , 51 , 72 ) indicate smaller gender disparities. Specifically, research from Denmark and South Korea found that men experience a smaller increase in suicide mortality risk following the suicide of a spouse or domestic partner’s suicide than women ( 46 , 72 ).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Agerbo found that among suicide-bereaved individuals in Denmark, men face a suicide mortality risk three times higher than that of women ( 47 ). However, subsequent studies ( 46 , 48 , 51 , 72 ) indicate smaller gender disparities. Specifically, research from Denmark and South Korea found that men experience a smaller increase in suicide mortality risk following the suicide of a spouse or domestic partner’s suicide than women ( 46 , 72 ).…”
Section: Resultsmentioning
confidence: 97%
“…However, subsequent studies ( 46 , 48 , 51 , 72 ) indicate smaller gender disparities. Specifically, research from Denmark and South Korea found that men experience a smaller increase in suicide mortality risk following the suicide of a spouse or domestic partner’s suicide than women ( 46 , 72 ). This pattern was similarly observed in Swedish men bereaved by a sibling’s suicide compared to women ( 51 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations